Resistance of Brutality in The Poems Your Way-Our Way-Truth by Zelda Quakawoot (2015), I Look At The World by Langston Hughes (2009), And Tribal Lines by Dan Davis (2000) - Haviza, Della; Anwar, Desvalini (Universitas Negeri Padang, 2024)
This research is an analysis of three poems by Zelda Quakawoot entitled Your Way- Our Way- Truth (2015), Langston Hughes entitled I Look at the World (2009), and Dan Davis entitled Tribal Lines (2000). This analysis explores the resistance of the Aboriginal people represented by the speakers in the three poems in obtaining their rights and justice. This resistance needs to be carried out by the Aboriginal people to fight the acts of brutality they experienced . An analysis of the three poems also reveals the extent of resistance Aboriginal people took against brutality. The study of these poems uses the concept of Post-Colonial theory by Edward Said. The results of this study indicate that the Aboriginal people already have the awareness to fight toward the acts of brutality that they experience. The analysis discusses: 1) Forms of brutality toward Aboriginal people, 2) impacts of brutality towards the lives of Aboriginal people, 3) Resistance made by Aboriginal people against brutality.